THE NASAL MUCOSA'S MORPHOFUNCTIONAL CHARACTERISTICS FOLLOWING SIMULTANEOUS SURGERY - Matkuliev Kh. M.; Saidakhmedova Sh. S.; Khakimov R. A.; Khodjaeva D. M.; Jabborov N. N. (Web of Journals Publishing, 2024)
The characteristics of the methods of checking the condition of the nasal mucosa after the combined surgical procedure performed in the nasal cavity are presented. Modern advances in medicine in the last decade allow expanding the scope of simultaneous operative procedures. Simultaneous (joint, at the same time) operations allow to eliminate several pathological conditions in the nose and paranasal sinuses at the same time. A strong curvature of the nasal septum is one of the most common local factors associated with the pathology of nasal cavities. Disruption of nasal breathing leads to changes in mucociliary clearance and creates conditions for inflammation in nasal cavities.
Keywords: nasal cavity, functional endoscopic sinus surgery (FESS), paranasal sinuses.